Bioactivity and bioaccessibility of bioactive compounds in gastrointestinal digestion of tomato bagasse extracts - Coelho, Marta (2022)
A nutrient-rich diet is a key to improving the chemical signals, such as antioxidants, which modulate pathogens’ resistance in the gut and prevent diseases. A current industrial problem is the generation of undervalued by-products, such as tomato bagasse, which are rich in bioactive compounds and of commercial interest (carotenoids and phenolic compounds). This work analyzed the effect of gastrointestinal digestion on the bioactivity and bioaccessibility of carotenoids and phenolic compounds from tomato bagasse extracts. Thus, the extraction by ohmic heating (OH) technology was compared with conventional (organic solvents). The results showed that the main phenolic compounds identified by UPLC-qTOF-MS were p-coumaric acid, naringenin, and luteolin. A higher recovery index for total phenolic compounds throughout the gastrointestinal digestion was observed for OH while for carotenoids, a strong reduction after stomach conditions was observed for both extracts. Furthermore, colon-available fraction exhibited a prebiotic effect upon different Bifidobacterium and Lactobacillus, but a strain-dependent and more accentuated effect on OH. Thus, the extraction technology highly influenced bioaccessibility, with OH demonstrating a positive impact on the recovery of bioactive compounds and related health benefits, such as antioxidant, anti-hypertensive, prebiotic, and anti-inflammatory properties. Of these properties, the last is demonstrated here for the first time.